Use of Micronutrients for Treatment of Idiopathic Abnormal Sperm Parameters - L. M. Elmahaishi; A. A. Abbas; M. S. Elmahaishi (Current Overview on Disease and Health Research Vol. 9, 2023)
The presnt study aimed to look at the possible effects of micronutrients on semen parameters including sperm count, motility, and morphology to improve male infertility. WHO defines infertility as the inability to achieve pregnancy within 12 months of regular sexual intercourse for couples in conception. Infertility affects 13–20% of couples in Poland and around the world, regardless of race or ethnicity. This study started from the 1st of March 2016 until 30th of November 2016 (6 six months was the period of taking the treatment) while the duration time of the study including the follow up and the examination period was 9 nine months. In this clinical trial included male subjects aged from 20 to 60 years with at least 1 year of infertility and abnormal semen analysis who received 3 -6 months’ treatment with a Cyclofert men that contains (l-carnitine l-tartarate 1g, N – Asetyl - cysteine 600 mg, 40 mg zinc, Lycopene 20 mg, 60 mg vitamin E, 200 mg vitamin C, 80 mg glutathione, 200 \(μ\)g selenium, 100 mg coenzyme Q10 and 400 \(μ\)g folic acid. Theses micronutrients were given in a form of two tablets/ twice a day for 6 months). Sperm parameters (count, motility, and morphology) and pregnancy incidence were monitored before and after treatment. After three and six months of treatment, the data gathered indicated that there was an overall progressive motility. Furthermore, compared to the untreated group, the sperm count rose by 64% after three months and 88% after six months (\(α\) = 0.00, 1, at P 0.05). Additionally, treatment for three and six months markedly improved the morphology of the sperm (p 0.05). Following six months of treatment, 30% of women were able to become pregnant thanks to these beneficial changes. However, the length of treatment has a direct correlation with each of these improvements. The pregnancy incidence has been increased compared to the untreated group. This treatment improved also the pregnancy status in which it caused an elevation in the number of pregnant spouses compared with untreated ones.